Re-purposing Ac/Ds transgenic system for CRISPR/dCas9 modulation of enhancers and non-coding RNAs in zebrafish - Chong-Morrison, V; Simoes, F; Senanayake, U; Carroll, D; Riley, P; Sauka-Spengler, T (2018)
Due to its genetic amenability coupled with recent advances in genome editing, the zebrafish serves as an excellent model to examine the function of both coding and non-coding elements. Recently, the non-coding genome has gained prominence due to its critical role in development and disease. Here, we have re-purposed the Ac/Ds maize transposition system to reliably screen and efficiently characterise zebrafish enhancers, with or without germline propagation. We further utilised the system to stably express guide RNAs in microinjected embryos enabling tissue-specific CRISPR/dCas9-interference (CRISPRi) knockdown of lncRNA and enhancer activity without disrupting the underlying genetic sequence. Our study highlights the utility of Ac/Ds transposition for transient epigenome modulation of non-coding elements in zebrafish.